Hitchhiking with forests: population genetics of the epiphytic lichen Lobaria pulmonaria in primeval and managed forests in southeastern Europe - Scheidegger, Christoph (Blackwell Publishing Ltd, 2012)
Availability of suitable trees is a primary determinant of range contractions and expansions of epiphytic species. However, switches between carrier tree species may blur co-phylogeographic patterns. We identified glacial refugia in southeastern Europe for the tree-colonizing lichen Lobaria pulmonaria, studied the importance of primeval forest reserves for the conservation of genetically diverse populations and analyzed differences in spatial genetic structure between primeval and managed forests with fungus-specific microsatellite markers. Populations belonged to either of two genepools or were admixed. Gene diversity was higher in primeval than in managed forests. At small distances up to 170 m, genotype diversity was lower in managed compared with primeval forests. We found significant associations between groups of tree species and two L. pulmonaria genepools, which may indicate “hitchhiking” of L. pulmonaria on forest communities during postglacial migration. Genepool B of L. pulmonaria was associated with European Beech (Fagus sylvatica) and we can hypothesize that genepool B survived the last glaciation associated within the refuge of European Beech on the Coastal and Central Dinarides. The allelic richness of genepool A was highest in the Alps, which is the evidence for a northern refuge of L. pulmonaria. Vicariant altitudinal distributions of the two genepools suggest intraspecific ecological differentiation.